2006
DOI: 10.1021/bi052162j
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Diversities among μ-Conotoxins Targeting TTX-resistant Sodium Channels

Abstract: mu-Conotoxins are peptides that block sodium channels. Molecular cloning was used to identify four novel mu-conotoxins: CnIIIA, CnIIIB, CIIIA, and MIIIA from Conus consors, C. catus and C. magus. A comparison of their sequences with those of previously characterized mu-conotoxins suggested that the new mu-conotoxins were likely to target tetrodotoxin-resistant (TTX-r) sodium channels. The four peptides were chemically synthesized, and their biological activities were characterized. The new conotoxins all block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 29 publications
2
42
0
1
Order By: Relevance
“…In contrast, none of the μ-conopeptides tested thus far has been found to block rat Na V 1.8 (Table 1). This is consistent with the observation that KIIIA (as well as CIIIA and CnIIIA) have minimal, if any, effects on TTX-resistant sodium currents (TTX-r I Na ), as a result of Na V 1.8, in rodent DRG neurons (15,24); similarly, SmIIIA does not block human Na V 1.8 expressed in oocytes (25). A Na V 1.9 clone was not available for testing in oocytes, and we have no information concerning its susceptibility to μ-conopeptides.…”
Section: Effects Of μ-Conopeptides On Propagated Action Potentials Insupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, none of the μ-conopeptides tested thus far has been found to block rat Na V 1.8 (Table 1). This is consistent with the observation that KIIIA (as well as CIIIA and CnIIIA) have minimal, if any, effects on TTX-resistant sodium currents (TTX-r I Na ), as a result of Na V 1.8, in rodent DRG neurons (15,24); similarly, SmIIIA does not block human Na V 1.8 expressed in oocytes (25). A Na V 1.9 clone was not available for testing in oocytes, and we have no information concerning its susceptibility to μ-conopeptides.…”
Section: Effects Of μ-Conopeptides On Propagated Action Potentials Insupporting
confidence: 90%
“…Discussion This is a comprehensive report of the susceptibilities of Na V 1.1 through 1.8 to the 11 μ-conopeptides used in this study. Previously, we reported that KIIIA, SIIIA, and SmIIIA (as well as CIIIA and CnIIIA) readily blocked TTX-resistant currents in neurons in frog sympathetic and dorsal root ganglion (DRG) neurons (23,24). In contrast, none of the μ-conopeptides tested thus far has been found to block rat Na V 1.8 (Table 1).…”
Section: Effects Of μ-Conopeptides On Propagated Action Potentials Inmentioning
confidence: 94%
“…In recent years, the Na v subtype selectivity of -conotoxins has been studied with renewed interest; many have now shown subtype selectivity for neuronal subtypes, including PIIIA, KIIIA, MIIIA, CIIIA, CnIIIA, CnIIIB, SIIIA, SmIIIA, and TIIIA. To date, no -conotoxins have been identified with affinity for the TTX-resistant mammalian subtypes Na v 1.5, -1.9, and -1.8 Schroeder et al, 2008;Leipold et al, 2011;Wilson et al, 2011a) despite a number showing activity at amphibian TTX-resistant isoforms (Zhang et al, 2006b) (see Table 5). The least susceptible isoforms include Na v 1.3, -1.7, and -1.5, and no -conotoxins have yet been found to block recombinantly expressed Na v 1.8 Schroeder et al, 2008;Leipold et al, 2011;Wilson et al, 2011a).…”
Section: A -Conotoxin Inhibitors Of Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…Всего на данный момент известно не менее 7 m-конотоксинов, ингибирующих ТТХ устойчивые натриевые каналы амфибий [63], и не менее двух, взаимодействующих на ТТХ устойчивые натриевые каналы млекопитающих [64].…”
Section: структура потенциалзависимых ионных каналов и разнообразие иunclassified